The relationship between upper extremity strength and performance in elite amputee football players - GURKAN GUNAYDIN (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪Despite having similar requirements to regular football, amputee football may also require different dynamics due to using crutches. This study investigated the relationship between upper extremity strength and performance in amputee players. Material and methods: ‪Twenty amputee players participated in this study. Running performance of amputee players was measured with sprint tests; aerobic performance with a shuttle run test; jumping performance with a one-leg hop test and upper extremity strength with a digital dynamometer. The relationship between the types of performance was evaluated by multiple regression analysis. Results: T‪he 10 (p = 0.009) and 20 meters sprint performance (p = 0.035) was associated with latissimus dorsi muscle and the 30 meters (p=0.030) with shoulder extension strength. In addition, 10 (p = 0.018), 20 (p = 0.020) and 30 meters sprint performance (p=0.036) was associated with one-leg hop performance. However, there were no related data with the max VO2 (p = 0.339), and the aerobic performance test duration (p = 0.348). Conclusions: ‪The results indicated that the sprinting performance of amputee players was not only related with lower extremity strength but also with upper extremity strength. It may be beneficial to include shoulder extension and particularly latissimus dorsi strengthening exercises in training programs of amputee football players to provide an increase in anaerobic performance.